EARLY DETECTION OF VERRUCOUS CARCINOMA USING METHYLENE BLUE STAINING IN SUSPECTED LEUKOPLAKIA LESION: A CASE REPORT: DETEKSI DINI KARSINOMA VERUKOSA MENGGUNAKAN PEWARNAAN METILEN BLUE PADA LESI TERDUGA LEUKOPLAKIA: LAPORAN KASUS - Rina Kartika Sari; Raziv Ganesha; Esti Kurniawati (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: Verrucous carcinoma is one of squamous cell carcinoma in the oral cavity which can caused by smoking, alcohol consumption, HPV etc. Verrucous carcinoma can mimick as pre cancer lesion such as leukoplakia, so that early detection is mandatory. Vital staining can be done by toluidine blue, but it reported toxic in organ. Methylene blue had similar chemical structure and exhibited similar physicochemical properties to toluidine blue.The aim of this case report is to report the case of early detection verrucous carcinoma using methylene blue in leukoplakia among smoker and alcoholic patient. Case: A 46-year-old male patient came to RSIGM Sultan Agung Semarang complaint that there was a wound on the left cheek that has not healed for the last 3 years. The wound was not painful but sore when exposed to food. The wound had been treated using Albothyl but there was no change. The patient had been an active smoker since 20 years ago and consume as much as 2-3 packs of cigarettes/day and also consumed alcohol about 4 years ago. Intraoral examination nodular white plaques, unscrappable with pigmentation areas and painless. Clinical diagnosis was nodular leukoplakia. Case Treatment: Early detection using methylene blue 1% was obtained and a positive dark blue indicated a change in malignancy. Patients were given symptomatic therapy of triamcinolone acetonide in orabase 0.1% then an excisional biopsy was performed and a histopathological appearance shows thickening and changes in polarity of the epithelial cells and dysplasia. The final diagnosis is verrucous carcinoma. Conclusion: The persistent white plaque with the risk factors of smoking and alcohol is a suspicion toward malignancy, early detection using methylene blue staining can performed before biopsy.